2020
DOI: 10.1161/cir.0000000000000896
|View full text |Cite
|
Sign up to set email alerts
|

Education, Implementation, and Teams: 2020 International Consensus on Cardiopulmonary Resuscitation and Emergency Cardiovascular Care Science With Treatment Recommendations

Abstract: For this 2020 International Consensus on Cardiopulmonary Resuscitation and Emergency Cardiovascular Care Science With Treatment Recommendations , the Education, Implementation, and Teams Task Force applied the population, intervention, comparator, outcome, study design, time frame format and performed 15 systematic reviews, applying the Grading of Recommendations, Assessment, Development, and Evaluation guidance. Furthermore, 4 scoping reviews and 7 evidence updates assessed any new evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
143
1
17

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 152 publications
(165 citation statements)
references
References 350 publications
4
143
1
17
Order By: Relevance
“…The 2020 International Liaison Committee on Resuscitation (ILCOR) Consensus on Science and Treatment Recommendation conditionally supported the use of termination of resuscitation (ToR) rules (verylow certainty evidence). 96 In making the recommendation, the ILCOR Education Implementation and Teams task force acknowledged variation in patient values, resources available, and performance of ToR rules across settings. The task force sought to balance the risk that implementation might result in missed survivors, against current variation in practice and improve termination decisions more generally.…”
Section: Termination Of Resuscitationmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2020 International Liaison Committee on Resuscitation (ILCOR) Consensus on Science and Treatment Recommendation conditionally supported the use of termination of resuscitation (ToR) rules (verylow certainty evidence). 96 In making the recommendation, the ILCOR Education Implementation and Teams task force acknowledged variation in patient values, resources available, and performance of ToR rules across settings. The task force sought to balance the risk that implementation might result in missed survivors, against current variation in practice and improve termination decisions more generally.…”
Section: Termination Of Resuscitationmentioning
confidence: 99%
“…125 The ILCOR Education, Implementation, and Teams (EIT) taskforce in their insights highlighted the need to consider local legislation. 96 There are important differences between the withholding or termination of resuscitation between the in-hospital and out-ofhospital setting. In the out-of-hospital setting, EMS teams often arrive at a scene where CPR is in progress, and then can only decide to withdraw (not withhold) resuscitation efforts.…”
Section: Termination Of Resuscitationmentioning
confidence: 99%
“…Automated feedback by machine could overcome the disadvantage of instructor's inaccurate feedback and it should be encouraged to add machine feedback into the instructor-led course during hands-on practice to improve the effectiveness of the training course. The 2020 ILCOR guideline also suggests the use of feedback devices that provide directive feedback on skill performance including compression rate, depth, recoil, and hand position during training courses 37 .…”
Section: Self-instruction (N = 32) Traditional Instruction (N = 32) Pmentioning
confidence: 99%
“…While the best timing for re-training is still under debate, a recent study showed that monthly training of CPR skills is a highly effective method to improve performance [45], although this can be di cult to implement due to time constraints. Therefore, mandatory yearly short competence refresher courses might be an easy way to better ensure the delivery of this early high-quality basic life support [25,44].…”
Section: Discussionmentioning
confidence: 99%
“…(4) state-of-the-art post-resuscitation care [24]; (5) performance-driven debrie ngs [25,26]; and (6) recording of the institution resuscitation success, with reporting of the results. These measures contribute to further optimisation of local procedures and maintain adherence to current guidelines [5,23].…”
Section: Introductionmentioning
confidence: 99%